Pidana Tutupan dalam RUU KUHP: dari Perspektif Tujuan Pemidanaan, Dapatkah Tercapai? (Undisclosed Penitentier in Criminal Code Bill: From the Purpose of Punishment’s Perspective, Can It Be Achieved?) - Lidya Suryani Widayati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2019)
Wetboek van Strafrecht (WvS) of 1915 did not regulate undisclosed penitentier. This criminal sanction is included in the Criminal Code (KUHP) through the establishment of Law Number 20 of 1946 on Undisclosed Penitentier. The legislators (the House of Representatives and the Government) re-arranged this criminal sanction in the Criminal Code Bill (RUU KUHP) as one of the main sanctions. This paper examines the policy of determining undisclosed penitentier from punishment perspective, especially from the purpose of punishment. Based on the purpose of punishment that is formulated in the Criminal Code Bill, the purpose of the punishment would not be achieved by using undisclosed penitentier. undisclosed penitentier also has the potential to cause discrimination because there is no standard for judges to impose these criminal sanctions. To provide legal certainty, the legislators should clearly formulate the criteria for judges to impose undisclosed penitentier. AbstrakWetboek van Strafrecht (WvS) tahun 1915 tidak mengatur sanksi pidana tutupan. Sanksi pidana ini dimuat dalam Kitab Undang-Undang Hukum Pidana (KUHP) melalui pembentukan Undang-Undang Nomor 20 Tahun 1946 tentang Hukuman Tutupan. Pembentuk Undang-Undang (DPR dan Pemerintah) kembali mengatur sanksi pidana ini dalam Rancangan Undang-Undang tentang Kitab Undang-Undang Hukum Pidana (RUU KUHP) sebagai salah satu pidana pokok. Tulisan ini mengkaji kebijakan penentuan pidana tutupan dari perspektif pemidanaan terutama dari tujuan pemidanaan. Berdasarkan pada tujuan pemidanaan yang dirumuskan dalam RUU KUHP maka tujuan pemidanaan tidak akan tercapai dengan menggunakan sarana pidana tutupan. Pidana tutupan juga berpotensi menimbulkan diskriminasi karena tidak ada ukuran bagi hakim untuk menjatuhkan sanksi pidana ini. Untuk memberikan kepastian hukum maka pembentuk undang-undang seharusnya merumuskan dengan jelas kriteria bagi hakim untuk menjatuhkan sanksi pidana tutupan.